Organometallic Magnets - Chandrasekhar, Vadapalli; Pointillart, Fabrice (Topics in Organometallic Chemistry, 2019)
This volume highlights the recent advances and state of art in the experimental and theoretical studies of organometallic magnets. A plethora of organic ligands such as Mannich-base derivatives, redox-active chromophores, cyanides, Schiff base among others are used to coordinate to 3d transition metals, 4f lanthanides and 5f actinides to design the molecular magnets. Deep analysis of the coordination sphere symmetry, electronic distribution, luminescence are investigated to perform magneto-structural correlation leading to a better understanding of the magnetic properties. Furthermore, the rationalization of the magnetic behavior can be reached using ab initio calculations. The multiple applications that these molecular magnets offer could revolutionize the high-density data storage, spintronics and quantum computing technologies. This volume provides a discussion of these topics from leading international experts and will be a useful reference for researchers working in this field.